Hypertrophic cardiomyopathy and Costello syndrome: review of recent related literature with case report - Osman Güvenç; Fatma Sevinç Şengül; Murat Saygı; Yakup Ergül; Alper Güzeltaş (KARE Publishing, 2014)
Costello syndrome is a rare syndrome characterized by failure to thrive, short stature, mental motor retardation, characteristic facial features, macrocephaly, a short neck, loose soft skin with deep palmar and plantar creases, and hypertrichosis. Cardiac involvement is seen in almost two thirds of patients, and is a determinant for the prognosis of Costello syndrome. The most common cardiac anomalies are pulmonary stenosis, hypertrophic cardiomyopathy, atrial septal defect, ventricular septal defect and arrhytmia. In this report, we present a 14-month-old female pediatric patient with hypertrophic cardiomyopathy, clinically and genetically diagnosed with Costello syndrome. The report also contains a review of recent related literature.